METHODOLOGY OF TEACHING USING ARTIFICIAL INTELLIGENCE IN GENERAL EDUCATION SCHOOLS (Symposium on Natural and Applied Sciences, 2026)
This article discusses the methodological foundations for using artificial intelligence technologies in the teaching process of general education schools. The study analyzes the possibilities of intelligent educational platforms for personalizing learning, monitoring students’ knowledge, and optimizing the educational process. The use of adaptive learning systems based on artificial intelligence helps increase students’ motivation and improve learning outcomes. The proposed methodology contributes to improving the quality of education through the effective integration of digital technologies.
Keywords: artificial intelligence, digital education, school education, interactive learning, educational technology, adaptive learning, learning analytics.